La orientación de las investigaciones de silvicultura para Latinoamérica - Wadsworth, F.H. (Instituto Interamericano de Ciencias Agrícolas (IICA), 2025)
Face with the urgency of solving pressing forest problems through adequate research, but limited "as to available" funds the countries of Latin America must set up priorities for research. In the field of silviculture of tropical mixed forest, first priority should be given to public lands where climax vegetation is forest and there is no conflict with other land use for timber production. Here the highest potentially productive area, screened through adequate productivity indexes, should be selected. Other possibilities may be considered whenever ther is compatibility with other proper land uses, such as increasing the "timber" output of areas suited primarily for conservation, recreation and wildlife. On highly productive areas, the choice of silvicultural practices to be investigated should take into account the conditions of the stand. In the upper story of an immature forest or one which has been highgraded, is adequate for high production, thinning schemes are in order. If inadequate, an evaluation of the existing regeneration will give the necessary dues as to what to do. If regeneration is plentiful liberation cuttings are in order; if not, removal of the whole stand followed by either natural regeneration, underplanting below nurse trees, or planting in full light are in order. Natural regeneration following clearcutting which may be practical for large areas, merits consideration even if the product may be presently of louer value per unit of area than from plantations. The qualification of "valuable tree" has to be adjusted to new markets which tend of favor light timbers. The upper canopy of most secondary forests in accessible areas presently has little value as to potential timber production but if natural regeneration under the existing canopy offers a minimum of 250 trees of valuable species, 10 to 30 cms. diameter per hectare, then it is worthwhite to concentrate on liberation cuttings rather than to substitute by planting. Using the favorable environment created by a high although useless, canopy, underplanting with some highly valuable species may be another alternative. Once the objective of producing well spaced stands of high quality timbers species is attained, research can move towards other goals such as investigating relationships between different sites, species and intensity of practices (including fertilization). Later, when poor stands become more common, pests and forest genetics will bear investigation.